Pengaruh Penggunaan Modul Berbasis Guided Inquiry terhadap Peningkatan Motivasi Belajar dan Kemampuan Berpikir Kritis Siswa - Permatasari, Pradina Andhin; Dwiastuti, Sri; Suwarno, Suwarno (Universitas Sebelas Maret, 2016)
This research aimed to reveal the effect of guided inquiry based learning module using on (1) improvement of student’s learning motivation, (2) improvement of student’s critical thinking skills, and (3) reveal the relationship between student’s learning motivation with student’s critical thinking skills. This research is considered as quasi experiment research, Pretest-Posttest with Control Group Design was used as research design to facilitate the data collection. Population of this research were all students in X grade of SMA N 1 Ngemplak, Boyolali. The sample of this research was established by Purposive Sampling. The samples were X-6 as experimental class and X-8 as control class. Experimental class has given guided inquiry based learning module as a treatment, while control class has not given guided inquiry based learning module. The data were collected using test (pre-test and post-test) and non-test (observation sheet, questionnaire, and documentation). Hypothesis was analyzed using ANOVA by SPSS 16 software with 0.05 significant index. The procedure of this research was planning, and data analysis. The results of this research showed that guided inquiry based learning module using had effect on improvement of student’s learning motivation and student’s critical thinking skills. Based on result of observation sheet and questionnaire, the percentage of experimental class’ learning motivation before a treatment was given is 67.2% as low category, after a treatment was given to, the percentage of experimental class’ learning motivation is 78.11% as enough category. The percentage of experimental class’ critical thinking skills from questionnaire before a treatment was given is 36.5% as low category, after a treatment was given to, the percentage of experimental class’ critical thinking is 73.42% as good category. The post-test score of experimental class was higher than control class’. Based on correlation analysis, student’s learning motivation had positive relationship with student’s critical thinking skills.Keywords: guided inquiry based learning module, learning motivation, critical thinking skills